Climate-Integrated Contingency Funding Plans for Indonesia's Big-Four Banks - Leonard Tiopan Panjaitan Panjaitan (Journal of Business, Finance, and Banking, 2026)
Climate change is a systemic macro-financial risk, yet quantitative frameworks integrating physical and transition climate risks into bank contingency funding planning remain limited, particularly in emerging markets like Indonesia. Methods: This study develops the Climate-Integrated Liquidity Coverage Ratio (CI-LCR) framework and applies it to Indonesia's Big-Four commercial banks (Bank Mandiri, Bank Rakyat Indonesia, Bank Central Asia, Bank Negara Indonesia). The empirical analysis utilizes a balanced panel (2018–2024), three NGFS climate scenarios, and ordinary least squares trend regression computed from a verified banking risk database. Results: In the worst-case scenario (Compound Climate Liquidity Stress), Bank Mandiri (94.00%) and Bank Rakyat Indonesia (92.50%) fall below the 100% regulatory minimum, whereas Bank Central Asia (212.63%) and Bank Negara Indonesia (117.62%) remain compliant. Corrected estimates show pre-2025 liquidity trajectories were statistically weak for all four banks. Furthermore, a disclosure assessment of fifteen banks reveals significant climate-governance weaknesses (average score 2.13 of 6). Conclusion: The proposed framework accordingly puts forward a dedicated climate transition liquidity buffer of 4.20 trillion Rupiah and a climate-based activation mechanism (C-TAT), providing a reproducible approach for integrating climate risk into Indonesian banking liquidity supervision